A survey on key management of zigbee network - Davani, Zavosh Abdollahzadeh (2013)
ZigBee is short distance, low complexity, and low power consumption wireless personal area network. As ZigBee has several applications in industry and healthcare, its security in the recent years has been attracting a lot of attention. This paper is a survey on key management of ZigBee network and model that proposed for enhancing key management of it. And also at the end, it suggests another way to enhancing the security of ZigBee network.